A revision of Centaurea sect. Cynaroides (Asteraceae, Cardueae—Centaureinae) - Negaresh, Kazem; Rahiminejad, Mohammad Reza (Phytotaxa, 2018)
The taxonomic status of the taxa known to belong to Centaurea sect. Cynaroides and its close relatives was revised on the basis of herbarium specimens from the authors’ expeditions and other collections. It is established that Boissier is the correct author for C. sect. Cynaroides, and C. regia is designated as a lectotype of this section. Thirty seven species are recognised in the section. Three new species (C. kamalnejadii, C. mozaffarianii, and C. zarrei), four new subspecies (C. amadanensis subsp. ranjbarii, C. cataonica subsp. syriaca, C. gigantea subsp. rechingeri, and C. kurdica subsp. ciliata) and two varieties (C. regia var. longispinosa and C. regia var. purpurea) are described. Two subspecies are reduced to the variety rank, and two varieties are elevated to the subspecies rank. Centaurea sect. Paraphysis is reduced as a synonym of C. sect. Cynaroides. Centaurea onopordifolia is transferred from C. sect. Cynaroides to a new section, i.e. C. sect. Cardueae. Three lectotypes are designated, six lectotypes from previous lectotypifications are rejected and the author names for six species are corrected. The recognized taxa, the relevant synonyms, type details, examined specimen lists, full descriptions and a taxonomic key are provided for this section. Distribution maps are provided for each sections, species, subspecies and varieties. Images of the type specimens of all taxa and also photos of the species in its natural habitat and related fields are provided. Five chromosome counts (2n = 18) are reported for C. amadanensis subsp. amadanensis, C. amadanensis subsp. gymnoclada, C. nemecii, C. regia var. regia, and C. regia var. purpurea. Biogeographical distribution and ecology of taxa of C. sect. Cynaroides are presented and discussed. In addition, cytotaxonomy, homoploidy and evolution of C. sect. Cynaroides are illustrated and discussed. Finally, the pollination of C. sect. Cynaroides is illustrated, and also images of the pollinators of some species of the section are provided.